Geosynchronous synthetic aperture radar: design and applications - Bruno, Davide (Cranfield University, 2009)
Synthetic Aperture Radar (SAR) imaging from geosynchronous orbit has significant potential advantages over conventional low-Earth orbit (LEO) radars, but also challenges to overcome. This thesis investigates both active and passive geosynchronous SAR configurations, presenting their different features and advantages. Following a system design trade-off that involved phase uncertainties, link budget, frequency and integration time, an L band bi-static configuration with 8-hour integration time that reuses the signal from a non-cooperative transmitter has been presented as a suitable solution. Cranfield Space Research Centre looked into this configuration and proposed the GeoSAR concept, an L band bi-static SAR based on the concept by Prati et al. (1998). It flies along a circular ground track orbit, reuses the signal coming from a noncooperative transmitter in GEO and achieves a spatial resolution of about 100 m. The present research contributes to the GeoSAR concept exploring the implications due to the 8-hour integration time and providing insights about its performance and its possible fields of application. Targets such as canopies change their backscattered phase on timescales of seconds due to their motion. On longer time scales, changes in dielectric properties of targets, Earth tides and perturbations in the structure of the atmosphere contribute to generate phase fluctuations in the collected signals. These phenomena bring temporal decorrelation and cause a reduction in SAR coherent integration gain. They have to be compensated for if useful images are to be provided. A SAR azimuth simulator has been developed to study the influence of temporal decorrelation on GeoSAR point spread function. The analysis shows that ionospheric delay is the major source of decorrelation; other effects, such as tropospheric delay and Earth tides, have to be dealt with but appear to be easier to handle. Two different options for GeoSAR interferometry have been discussed. The system is well suited to differential interferometry, due to the short perpendicular baseline induced by the geometry. A GeoSAR has advantages over a Low Earth Orbit (LEO) SAR system to monitor processes with significant variability over daily or shorter timescales (e.g. soil moisture variation). This potential justifies further study of the concept.